ARTIKEL REVIEW: KARAKTERISTIK DAN EVALUASI SEDIAAN TABLET EFFERVESCENT - Cahyani, Mesya Pramesti Regita; Rodiyah, Siti; Prasetyo, Muhammad Angga; Rahmawati, Dewi; Zhihrotulwida, Dzakiya; Mubarak, M. Fithrul (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
ABSTRACT Effervescent tablets are a pharmaceutical dosage form that is increasingly popular due to their practicality, ease of consumption, and ability to improve medication adherence and absorption. The purpose of reviewing articles is to determine the characteristics and evaluation of effervescent tablet preparations, including formulations, physical properties and physical quality evaluation of effervescent tablets. The method used in writing this article is the 2019-2025 literature study search method. National and international scientific articles were reviewed and examined regarding the formulation and evaluation of effervescent tablets made from herbal and natural ingredients. The data were systematically analyzed to identify physical parameters, ingredient variations, and key factors influencing the quality and success of the formulation. The results show that the formulation of effervescent tablets from herbal ingredients such as noni, meniran, and katuk leaves can meet the established physical and quality standards, especially on parameters such as hardness, dissolving time, and stability. Some formulas show optimal results, although optimization still needs to be done on certain parameters such as size uniformity and friability to meet pharmacopoeial standards. In addition, production process factors such as humidity also affect the dissolving time and final quality of effervescent tablets. ABSTRAK Tablet effervescent merupakan bentuk sediaan farmasi yang semakin populer karena kepraktisannya, kemudahan konsumsi, serta kemampuannya untuk meningkatkan kepatuhan dan penyerapan obat. Tujuan meriview artikel adalah untuk mengetahui karakteristik dan evaluasi sediaan tablet effervescent, termasuk formulasi, sifat fisik dan evaluasi mutu fisik Tablet effervescent. Metode yang digunakan dalam penulisan artikel ini adalah metode penelusuran studi pustaka tahun 2019-2025. Artikel-artikel ilmiah nasional dan internasional ditelaah dan dikaji mengenai formulasi dan evaluasi tablet effervescent berbahan herbal dan alami. Data dianalisis secara sistematis untuk mengidentifikasi parameter fisik, variasi bahan, dan faktor-faktor yang memengaruhi mutu dan keberhasilan sediaan. Hasil menunjukkan bahwa formulasi tablet effervescent dari bahan herbal seperti mengkudu, meniran, dan daun katuk dapat memenuhi standar fisik dan mutu yang ditetapkan, terutama pada parameter seperti kekerasan, waktu larut, dan kestabilan. Beberapa formula menunjukkan hasil yang optimal, meskipun masih perlu dilakukan pengoptimalan pada parameter tertentu seperti keseragaman ukuran dan friabilitas agar memenuhi standar farmakope. Selain itu, faktor proses produksi seperti kelembaban juga mempengaruhi waktu larut dan kualitas akhir tablet effervescent.